Pharmacokinetic/Pharmacodynamic Analysis of Oral Calcium Fosfomycin: Are Urine Levels Sufficient to Ensure Efficacy for Urinary Tract Infections? - Alicia Rodríguez-Gascón; Ana Alarcia-Lacalle; María Ángeles Solinís; Ana del Pozo-Rodríguez; Zuriñe Abajo; María Cabero; Andrés Canut; Arantxa Isla (MDPI AG, 2023)
Urinary tract infections (UTIs) are extremely common and a major driver for the use of antimicrobials. Calcium fosfomycin is an old antibiotic indicated for the treatment of UTIs; however, data about its urine pharmacokinetic profile are scarce. In this work, we have evaluated the pharmacokinetics of fosfomycin from urine concentrations after oral administration of calcium fosfomycin to healthy women. Moreover, we have assessed, by pharmacokinetic/pharmacodynamic (PK/PD) analysis and Monte Carlo simulations, its effectiveness considering the susceptibility profile of Escherichia coli, the main pathogen involved in UTIs. The accumulated fraction of fosfomycin excreted in urine was around 18%, consistent with its low oral bioavailability and its almost exclusively renal clearance by glomerular filtration as unchanged drug. PK/PD breakpoints resulted to be 8, 16, and 32 mg/L for a single dose of 500 mg, a single dose of 1000 mg, and 1000 mg q8h for 3 days, respectively. For empiric treatment, the estimated probability of treatment success was very high (>95%) with the three dose regimens, considering the susceptibility profile of E. coli reported by EUCAST. Our results show that oral calcium fosfomycin at a dose level of 1000 mg every 8 h provides urine concentrations sufficient to ensure efficacy for the treatment of UTIs in women.